2021
DOI: 10.3390/geriatrics6010018
|View full text |Cite
|
Sign up to set email alerts
|

The Seniors’ Community Hub: An Integrated Model of Care for the Identification and Management of Frailty in Primary Care

Abstract: (1) Background: Integrated models of primary care deliver the comprehensive and preventative approach needed to identify and manage frailty in older people. Seniors’ Community Hub (SCH) was developed to deliver person-centered, evidence-informed, coordinated, and integrated care services to older community dwelling adults living with frailty. This paper aims to describe the SCH model, and to present patient-oriented results of the pilot. (2) Methods: SCH was piloted in an academic clinic with six family physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…However, quantitative evidence for clinical outcomes, patient satisfaction or cost-effectiveness of these staff-intensive models is lacking. A Canadian feasibility study of a similar service provided through PCNs failed to show positive benefits on gait speed or patient related outcomes [ 39 ]. A recent feasibility study of modified CGAs delivieried within Scottish general practice suggested that this approach could reduce hospital admissions, but GP workload was also increased, over the first six months [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, quantitative evidence for clinical outcomes, patient satisfaction or cost-effectiveness of these staff-intensive models is lacking. A Canadian feasibility study of a similar service provided through PCNs failed to show positive benefits on gait speed or patient related outcomes [ 39 ]. A recent feasibility study of modified CGAs delivieried within Scottish general practice suggested that this approach could reduce hospital admissions, but GP workload was also increased, over the first six months [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Involving various organizations can provide rural people with numerous resources, such as people, places, and financial support, to continue social prescribing. The continuous provision of social prescribing can be ensured via collaboration with various organizations, as this can lead to the development of sustainable communities and comprehensive care in rural communities [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as this study focused only on the comprehensiveness of medical care, it did not show the effectiveness of family medicine in improving patients’ and citizens’ health outcomes in communities. Previous studies have suggested that comprehensiveness through family medicine has a significant effect on patient satisfaction and medical cost; however, research on the relationship between comprehensive care and health outcomes is scant [ 43 , 48 , 49 ]. Thus, future research should investigate this relationship.…”
Section: Discussionmentioning
confidence: 99%